Penggunaan Metode Kaizen Pada Tahap Improve Dalam Six Sigma - Yuliana Yuliana; Yuki Novia Nasution; Wasono Wasono (EKSPONENSIAL, 2017)
Six sigma is a holistic approach to solve the cause of disabilityproductsproblems and improve processes through the DMAIC (Define, Measure, Analyze, Improve, Control). Analyze the causes of product defect using the proposed improvement of Kaizen that is Five-M Checklist, 5W+1H (What, Why, Where, When, When, Who, How), and Five Step Plans. Obtained a better quality thereby creating customer satisfaction. The purpose of this study were to determine the value of Defect Per Million Opportunities (DPMO), Critical To Quality (CTQ) products, and know the process of production of bottled water brand RAMA volume 220ml. The result showed DPMO value 45.808. The level of the company be at 3,186 sigma with Critical To Quality (CTQ) is lid at 41,3%, water volume at 27,1%, and glass at 25%. The p-chart is used before and after improvement in this study to analyze the number of defective product. The result showed that before the repair using analysis of Kaizen, there is a lot of data out of the control limits, whereas after repair using analysis of Kaizen there is no data out of the control limits and some data products were near the centerline of the control p-chart.